An evaluation of a toothbrushing programme in schools. Issue 6 (30th September 2014) - Woodall, James; Woodward, Jenny; Witty, Karl; McCulloch, Shona
Abstract : Purpose: – The purpose of this paper is to assess the effectiveness of a toothbrushing intervention delivered in primary schools in Yorkshire and the Humber, a Northern district of England. The toothbrushing intervention was designed with the intention of improving the oral health of young children. The paper reports the effectiveness of the intervention and explores process issues related to its co-ordination and delivery. Design/methodology/approach: – The evaluation had three data gathering approaches. These were: in-depth case studies of three selected schools participating in the toothbrushing programme; interviews with oral health promoters responsible for the programme in the district; and a small scale questionnaire-based survey which was sent to the 18 schools participating in the intervention. Findings: – The intervention was accepted by children and they enjoyed participating in the toothbrushing scheme. Children had often become more knowledgeable about toothbrushing and the consequences of not regularly cleaning their teeth. The scheme was contingent on key staff in the school and the programme was more successful where school's embraced, rather than rejected the notion of improving children's health alongside educational attainment. Whether the intervention made differences to brushing in the home requires further investigation, but there is a possibility that children can act as positive "change agents" with siblings and other family members. Practical implications: – This paper suggests that schools can be an effective setting for implementing toothbrushing interventions. Originality/value: – Toothbrushing in schools programmes are a relatively new initiative that have not been fully explored, especially using qualitative approaches or focusing on the views of children. This paper makes a particular contribution to understanding the process and delivery of toothbrushing interventions delivered in primary schools. The implications for programmes outside of the UK context are discussed.